Cross-Cultural Translation and Psychometric Properties Study of Aberrant Behavior Checklist-Community, Thai Version - นาคพงศ์พันธุ์, อัศวิน; ชาญศิลป์, ชวนันท์ (Journal of the Psychiatric Association of Thailand, 2019)
Objectives : To translate Aberrant behavior Checklist-community (ABC-C) by cross-cultural translation principle into Thai Version and examine its psychometric properties Methods : In this study, Aberrant behavior Checklist-community (ABC-C) was translated by cross-cultural translation principle to be more in accordance with Thai culture. Following back - forth translation and discussion about Semantic, Idiomatic, Experential and Conceptual equivalence by child and adolescent psychiatry specialists and English translator experts, ABC-C last adaptation was made by cognitive debriefing and the Psychometric properties such as internal consistency ,inter and intra-rater reliability and concurrent validity were measured by 2 observers observing activities of 40 autistic spectrum disorder and intellectual disability subjects simultaneously for 1 hour to reduce recall bias Results : ABC-C Thai version has high internal consistency (α = 0.922), while inter-rater and test-retest reliability are still high [ICC = 0.90 (95% CI: 0.81-0.95)] and [ICC = 0.92 (95% CI: 0.86-0.96)] respectively. When compared with the Clinical Global Impression-Severity Scale (CGI-S) for concurrent validity, the result also showed high positive correlation (r = 0.87; p < 0.01). Conclusions : The outcome was shown that ABC-C Thai version has high qualities and is appropriate to apply for both healthcare services and further study in this group of patients.